Quality assessment of plantain (Musa paradisiaca L.) as affected by different ripening methods - Adewole, M. B.; Duruji, R. W. (African Journal of Biotechnology, 2023)
INTERNATIONAL JOURNAL OF African Journal of Biotechnology,VOLUME: 9(38), pp. 6290-6293